Bacteriological quality of irrigation water from vegetable gardens in the municipalities of Araraquara, Boa Esperança do Sul and Ibitinga, SP - Beraldo, Rosa Maria [UNESP]; Farache Filho, Adalberto [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
This work aimed to assess the bacteriological quality of water used in the irrigation of vegetable gardens in the municipalities of Araraquara, Boa Esperança do Sul and Ibitinga, São Paulo, Brazil. A total of 80 samples of water used in the irrigation of 40 vegetable gardens were analyzed, two samples coming from each vegetable garden. They were collected at the same site in different months, which resulted in two sample collection groups. The most probable number (MPN/100mL) of total coliforms, thermotolerant coliforms and enterococci was identifi ed by means of the multiple tube technique. The analysis of the fi rst group samples showed quantities of thermotolerant coliforms above the amount allowed by current law for irrigation water (CONAMA Resolution n. 357) in nine cases. The owners of those vegetable gardens were then instructed in water disinfection procedures. After the analysis of the second group samples, it was noticed that only one sample did not meet the quality standards, and it was collected at a site where no disinfection procedure had been carried out. According to the results, 77.5% of the vegetable gardens were using water whose samples meet the quality standards. After the owners were instructed with regard to disinfection procedures, that number changed to 97.5%, which confi rms the importance of controlling and supervising irrigation water quality

O objetivo deste trabalho foi avaliar a qualidade bacteriológica de águas utilizadas na irrigação de hortas nos municípios de Araraquara, Boa Esperança do Sul e Ibitinga, SP. Foram analisadas 80 amostras de águas utilizadas na irrigação de 40 hortas, sendo duas amostras de cada horta, coletadas no mesmo ponto e em diferentes meses, caracterizando dois grupos de coleta. Foi determinado o número mais provável (NMP/ 100mL) de coliformes totais, coliformes termotolerantes e enterococos, através da técnica dos tubos múltiplos. Após a análise das amostras referentes à primeira coleta, observou-se a presença de coliformes termotolerantes em quantidades acima da permitida pela legislação vigente para águas destinadas à irrigação (Resolução CONAMA n.357) em nove casos. Os proprietários dessas hortas foram orientados sobre medidas de desinfecção das águas e, após a análise das amostras referentes à segunda coleta, observou-se que apenas uma continuou fora do padrão de qualidade, sendo esta obtida em um ponto de coleta no qual não foi realizado nenhum procedimento de desinfecção. De acordo com os resultados, 77,5% das hortas utilizam águas cujas amostras atendem ao padrão de qualidade e após a intervenção junto aos proprietários este valor sobe para 97,5%, o que confi rma a importância da fi scalização e controle da qualidade da água empregada na irrigação.
Qualidade bacteriológica de águas de irrigação de hortas nos municípios de Araraquara, Boa Esperança do Sul e Ibitinga, SP
Keywords: Vegetables; Irrigation; Water; Coliforms; Enterococci; Hortaliças; Água de irrigação; Coliformes; Enterococos